Study on the Reinforcing Effects of the FRP-PCM Method on Tunnel Linings for Dynamic Strengthening. (7th October 2021) - Wang, Xiaoshan; Wei, Lin; Wang, Zaiquan; Jiang, Yujing; Zhang, Liming; Meng, Fanzhen; Cong, Yu
Abstract : In recent years, fiber-reinforced plastic (FRP) has been widely used in the reinforcement of concrete structure fields due to its favorable properties such as high strength, low weight, easy handling and application, and immunity to corrosion, and the reinforcing effects with FRP grids on tunnel linings should be quantitatively evaluated when the tunnels encounter an earthquake. The aim of the present study is to estimate the reinforcing effects of fiber-reinforced plastic (FRP) grids embedded in Polymer Cement Mortar (PCM) shotcrete (FRP-PCM method) on tunnel linings under the dynamic load. A series of numerical simulations were performed to analyze the reinforcing effects of FRP-PCM method quantitatively, taking into account the impacts of tunnel construction method and cavity location. The results showed that the failure region on lining concrete is improved obviously when the type CII ground is encountered, regardless the influences of construction method and cavity location. With the increment of ground class from CII to DII, the axial stress reduction rate R σ increases from 13.18% to 48.60% for tunnels constructed by the NATM, while for those tunnels constructed by the NATM, R σ merely varies from 0.72% to 2.11%. R σ decreases from 43.35% to 34.80% when a cavity exists on the shoulder of lining, while decreasing from 14.7% to 0.12% when a cavity exists on the crown of lining concrete. All those conclusions could provide valuable guidance for the reinforcing of underground structures.